Bicuspid Aortic Valve and Sudden Cardiac Death - Cecilia Salzillo; Andrea Quaranta; Fabrizia Di Lizia; Michela Lombardo; Marco Matteo Ciccone; Vincenzo Ezio Santobuono; Enrica Macorano; Francesco Introna; Biagio Solarino; Andrea Marzullo (Life, 2025)
Bicuspid aortic valve (BAV) is the most common congenital heart anomaly, affecting an estimated 0.5% to 0.77% of the general population. This condition occurs when the aortic valve has only two cusps instead of the usual three, disrupting normal valve function and increasing the risk of various cardiovascular diseases. Often asymptomatic in its early stages, BAV can gradually progress, leading to stenosis, valve insufficiency, and abnormalities of the ascending aorta. One particularly concerning aspect is its potential association with sudden cardiac death (SCD). The aim of this literature review is to examine the relationship between BAV and the risk of SCD, highlighting the pathogenic variants and pathophysiological mechanisms involved while emphasizing the significance of valve classification and its clinical implications. Additionally, it explores current research gaps and future directions to enhance early identification of at-risk individuals and reduce the incidence of SCD.